Accounting problems in small companies / Arun Mohamed - Mohamed, Arun (1987)
The title of this report is ’Accounting Problems in Small Companies'. The main .objective of the report, as its title explains is to look into the problems of accounting practice in the small companies in the context of Malaysian environment. Each problem is discussed with examples given and at the end of the report there are several recommendations forwarded as potential solutions to the problems.